Petrology and geochemistry of the basal gabbro unit, Uitkomst complex - Strauss, Toby Anthony Lavery (Rhodes University, Faculty of Science, Department of Geology, 1996)
The Cu/(Cu+Ni) ratios associated with the Basal Gabbro also display the vertical reverse fractionation trend, supporting the supercooled margin model. The disseminated sulphides in the lowermost units, are regarded as being the result of sulphur saturation induced by contamination from the dolomitic and quartzitic xenoliths. This is supported by isotope data which indicate the high degree of contamination in the lowermost units of the Complex. The results of this study are used to propose a model for the petrogenesis and metallogenesis of the Uitkomst Complex, whereby the Complex is closely related to the Bushveld Complex. The Basal Gabbro, as supported by its chemistry and style of mineralisation (Cu-rich), represents a supercooled margin to the lowermost units of the Uitkomst Complex, which stoped upwards into the surrounding sediments, assimilating the country rock xenoliths, and precipitating sulphides. Following this was a period in which large quantities of magma moved laterally through the system before the magma flow waned, and closed system crystallisation ensued. As the body cooled, the primarily magmatic water was superceded by the hydrothermal magmatic water released from the xenoliths, and later by geothermally driven circulating meteoric water, producing the extensive alteration. This alteration was accompanied by considerable stress and the development of fractures and shears. Finally the Complex was itself intruded by diabase sills and later dolerite dykes.
Keywords: Petrology -- South Africa -- Mpumalanga -- badplaas; Geochemistry -- South Africa -- Mpumalanga; Gabbro -- South Africa -- Mpumalanga